Village Financial Transparency And Accountability (Empirical Study in Disadvantaged Villages in West Halmahera Regency) - Suwito SUWITO; Abdul Rahman JANNANG (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to reveal the application of the principles of Transparency and Accountability in the administration of Village Government which is categorized as Disadvantaged in West Halmahera Regency. Transparency is related to information disclosure which is built on the freedom to obtain information related to the general interest of the village, which can be directly obtained by villagers who need it. While accountability realizes the obligation of the Village to account for and explain the process and achievement of financial and non-financial goals to Village residents. By practicing the concepts of transparency and accountability in village financial management, it is expected to create various positive influences for improving the quality of life and welfare of the Village Community. Researchers used a qualitative approach with descriptive analysis methods to achieve these goals. The results showed that the conditions for implementing transparency and accountability in Ulo Village, Jailolo District, Tewe Village, South Jailolo District and Togoreba Tua in North Ibu District were generally quite good. In addition, this study also found that in general there is evidence that the condition of underdeveloped villages in the three villages often results in a slowdown in the achievement of village performance; This is more because there are complex socio-cultural disputes between villagers and the village government.